An Engraved Human Bone from the Mesolithic–Neolithic Site of Lepenski Vir (Serbia). Issue 2 (6th April 2016) - Wallduck, Rosalind; Bello, Silvia M.
Abstract : Post-mortem manipulations of the body were common at Mesolithic–Neolithic sites along the Danube River. During assessment of disarticulated human remains from Lepenski Vir, an unusual set of incisions (notches) were observed on the diaphysis of a human left radius along with a few cut-marks. Very few studies have attempted to distinguish clearly the characteristics of these modifications. All incisions were examined using a Scanning Electron Microscope and a Focus Variation Microscope that generated measurable three-dimensional digital models. Our results indicate that, on the basis of their micro-morphometric features, qualitative and quantitative distinctions can be made between cut-marks and notches, a methodology which can be applied to other engraved bones. Cut-marks, accidentally produced during flesh removal, were more irregular, longer, narrower and shallower than the notches. The notches, produced by a 'nick and slice' motion (pressure was applied to the bone, then the tool was pulled in one direction), were deliberately engraved. This engraved human bone is a rare example within a Prehistoric European context, possibly a form of notation, marking or counting a series of (important) events.